1995
DOI: 10.1007/bf02577854
|View full text |Cite
|
Sign up to set email alerts
|

Fuel properties of tallow and soybean oil esters

Abstract: Fuel properties of beef tallow, soybean oil, their esters, and blends with No. 2 diesel fuel and ethanol were determined. Fuel properties tested were viscosity, specific gravity, API gravity, distillation ranges, calculated cetane index, energy content, flash point, water content, sulfur content, carbon residue, particulate matter, acid value, copper-strip corrosion test, ash content, melting point, cloud point, and pour point. Gas-chromatographic analyses of tallow, soybean oil, and their esters were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(81 citation statements)
references
References 7 publications
8
69
0
4
Order By: Relevance
“…Results from this present study are comparable to those earlier reported. Ali et al (1995) reported the following properties for biodiesel produced from soybean oil: kinematic viscosity, 4.5 mm 2 /s; cloud point, 1 o C; pour point, -7 o C; flash point, 178 o C and density, 885 kg/m 3 . Boocock et al (1998) carried out transesterification of soybean oil with methanol at different concentrations of sodium hydroxide.…”
Section: Discussionmentioning
confidence: 99%
“…Results from this present study are comparable to those earlier reported. Ali et al (1995) reported the following properties for biodiesel produced from soybean oil: kinematic viscosity, 4.5 mm 2 /s; cloud point, 1 o C; pour point, -7 o C; flash point, 178 o C and density, 885 kg/m 3 . Boocock et al (1998) carried out transesterification of soybean oil with methanol at different concentrations of sodium hydroxide.…”
Section: Discussionmentioning
confidence: 99%
“…Process efficiency of transesterification depends on several factors like the type of catalyst, temperature, alcohol to oil ratio, water and free fatty acid content, etc. (24).…”
Section: Transesterification As a Methods For Biodiesel Productionmentioning
confidence: 99%
“…In this work, cloud point was evaluated as the temperature at which wax crystals are formed (Ali et al 1995) and pour point as the lowest temperature at which a fuel can flow (Lee et al 1995). This parameter is directly related to the fatty acid composition of the sample, the higher the unsaturation rate, the lower the cloud point.…”
Section: Cloud and Pour Pointmentioning
confidence: 99%